Rugby morphologies: "bigger and taller", reflects an early directional selection - Sedeaud, A.; Vidalin, H.; Tafflet, M.; Marc, A.; Toussaint, J.-F. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of this paper was to investigate the changes over time in anthropometric parameters of young and adult rugby players in France. Methods: Age, mass and height were collected for 2051 French elite rugby players participating in the championship during the 1988-1989 and the 2008-2009 seasons. The same variables were collected for the best 145 juniors (under 21 years) and 448 U15 (under 15 years) French players for these seasons. Changes in anthropometric parameters were compared according to age, category (back vs. forwards) and season. Results: Over 20 years, adult French rugby backs and forwards have become heavier by 12 kg and 12.3 kg, taller by 5.4 cm and 2.9 cm, respectively. Junior players also became taller and heavier, 6 cm and 9.9 kg for backs and 4.4 cm and 11.1 kg for forwards. U15 backs have gained 5.1 cm and 6.5 kg, and forwards earned 4.7 cm and 4.7 kg. Conclusion: Rugby players have become taller and heavier. Their current morphology is the product of a long process of competition and selection. This study demonstrates that this selection of the "large sizes" is already present at a young age.